Mesostichon with a Project-Based Learning Model in German Subject at Class XI of SMAN 1 Lawang - Khoirotul Ummah; Herri Akhmad Bukhori (Universitas Negeri Malang, 2021)
The purpose of this study was to explain the activities and responses of students to the application of the Mesostichon with a project-based learning model in learning literary works according to KD 3.5 and 4.5 in class XI IBB SMAN 1 Lawang. This study used the research approach was descriptive qualitative. There are two techniques used to collect the data, namely observation and interviews. The supporting instruments in this study were the observation sheet and interview guidelines as tools for collecting data. the activities of students during the learning process of the German language got positive results and the responses given by students are in a good category. Students optimally apply their ideas, creativity, and writing skills. This can be seen from the results, it is based on the characteristics possessed by Mesostichon. The application of project-based learning models to support independent learning and increase learning motivation and student interest.Based on the results of interviews with students, project-based learning did not make them bored, it increases the activity and motivation of students in learning.